Ensuring standardized parameters for the transmission of digital signals by twisted pairs at the technological stage of manufacturing cables for industrial operating technologies - Bezprozvannych, G. V.; Pushkar, O. A. (Національний технічний університет "Харківський політехнічний інститут", 2023)
In production control and control systems, buildings use many simple devices - sensors to detect light, heat, movement, smoke, humidity and pressure, mechanisms for activation and control of switches, closing devices, alarm, etc. - «operating technologies» (OT). Different communication protocols and field tire technologies, such as Modbus for conditioning systems, Bacnet for access control and Lonworks for lighting, have been traditionally used and used for their connection. Network fragmentation leads to the need to use gateways to transform protocols when creating a single automation system, which complicates the implementation of complex control systems for any object. At the same time, information networks are unified, but the Ethernet protocol used in them for operating technologies for various reasons (technological, cost) has not been widespread. Due to its high bandwidth compared to existing field tire networks, industrial Ethernet is significantly capable of increasing flexibility in the implementation of additional functions in OT. Modern industrial Ethernet networks are based on non-shielded and shielded twisted pair category 5e cables. The presence of additional metal screens in the structure of twisted pair causes the increase in electrical resistance of conductors due to the effect of closeness, the electrical capacity, and the ratio of attenuation in the range of transmission of broadband signals. Purpose. Substantiation of the range of settings of technological equipment to ensure standardized values of the extinction coefficient and immunity based on the analysis of the results of measurements in a wide frequency range of electrical parameters of shielded and unshielded cables for industrial operating technologies. Methodology. Experimental studies have been performed for statistically averaged electrical parameters of the transmission of pairs for 10 and 85 samples of 305 m long and shielded cables of category 5e, respectively. It is determined that in the frequency range from 1 to 10 MHz, unshielded cables have less values of the attenuation coefficient. In the range of more than 30 MHz, the shielded cables have smaller values of the attenuation due to the influence of the alumopolymer tape screen. It is established that the coefficient of paired correlation between asymmetries of resistance and capacity of twisted pairs is 0,9735 - for unshielded and 0,9257 - for shielded cables. The impact has been proven to a greater extent asymmetry of resistance the pairs on the increasing noise immunity of cables. The influence noise interference on the deviation of the diameter and electrical capacity of the isolated conductor from the nominal values in the stochastic technological process is analyzed. The strategy of technological process settings to ensure the attenuation and the noise immunity in the high-frequency range is substantiated. Practical value. Multiplicative interference, caused by random changes in the stochastic technological process, can lead to a deviation of diameter 2 times from the nominal value at level of probability at 50 %. The equipment settings of the technological equipment must guarantee the coefficient of variation capacity of the insulated conductor at 0.3 % for high level of noise immunity.

Сучасні мережі промислового Ethernet засновані на витих парах неекранованих та екранованих кабелів категорії 5е. Впровадження однопарного Ethernet стикається з проблемою забезпечення передачі цифрових сигналів на відстань до 1000 м зі швидкістю до 1 ГБіт/с. Виконано експериментальні дослідження статистично усереднених електричних параметрів передачі витих пар для 10 і 85 вибірок бухт довжиною 305 м неекранованих та екранованих кабелів категорії 5е відповідно. Визначено, що у діапазоні частоти від 1 до 10 МГц неекрановані кабелі мають менші значення коефіцієнту згасання. У діапазоні більше 30 МГц екрановані кабелі мають менші значення коефіцієнту згасання, що обумовлено впливом алюмополімерного екрану. Встановлено, що коефіцієнт парної кореляції між омічною та ємнісною асиметріями витих пар дорівнює 0,9735 – для неекранованого та 0,9257 – для екранованого кабелів. Доведено вплив у більшій мірі омічної асиметрії витих пар на завадостійкість кабелів. Проаналізовано вплив адитивної та мультиплікативної завад на відхилення діаметру та ємності ізольованого провідника від номінальних значень у стохастичному технологічному процесі. Обґрунтовано діапазони налаштувань технологічного процесу для забезпечення нормованих значень коефіцієнту згасання та завадостійкості витих пар у високочастотному діапазоні.
Keywords: industrial Ethernet; twisted pair; ratio of attenuation; noise immunity; ohmic and capacitive asymmetry; stochastic technological process; additive and multiplicative interference; coefficient of variation; промисловий Ethernet; вита пара; коефіцієнт згасання; завадостійкість; омічна та ємнісна асиметрії; стохастичний технологічний процес; адитивна та мультиплікативна завади; коефіцієнт варіації